Nodavirus encephalopathy in turbot (Scophthalmus maximus): inflammation, nitric oxide production and effect of anti-inflammatory compounds [Poster] - Montes, Ariana; Poisa Beiro, Laura; Figueras Huerta, Antonio; Novoa, Beatriz (2010)
8th International Symposium on Viruses of Lower Vertebrates, Santiago de Compostela (España), 26-29 abril 2010 No